Development and evaluation of a mobile thermotherapy technology for in-field treatment of Huanglongbing (HLB) affected trees - Ghatrehsamani, Shirin; Abdulridha, Jaafar; Balafoutis, Athanasios; Zhang, Xiuhua; Ehsani, Reza; Ampatzidis, Yiannis (Biosystems engineering, 2019)
Thermotherapy, as a non-chemical method to treat pests, has many advantages over the conventional chemical methods for treating some plant diseases. However, applying this method in the field, especially in orchards, can be difficult due to technical complications with regards to total coverage of large trees. In this work, a mobile thermotherapy system was designed and developed to provide heat treatment to individual citrus trees infected with Huanglongbing (HLB) disease. Based on previous studies, the system was designed to produce heat inside a canopy cover that covered a whole citrus tree, raising the internal temperature to 54 °C and treating the tree for 90 s. The system was able to increase the heat inside the canopy cover using different heat sources by either releasing steam or a combination of steam and hot water. A series of experiments were conducted to assess the uniformity of heat distribution within the tree canopy and the time to reach an appropriate temperature utilising two treatment types: Steam Treatment (ST) and Hot Water & Steam Treatment (HWST). Results indicated that the uniformity of heat is similar with both treatment types, while the average time for the entire treating process was 63% shorter when using HWST compared to ST. Furthermore, HWST reduced energy consumption by 52% compared to ST. The present study focuses on the technical evaluation of an thermotherapy system and does not evaluate the treatment efficiency and tree condition after treatment, which will be the subject of future experimental work. •A mobile thermotherapy technology was developed for citrus trees.•Steam Treatment (ST) and Hot water & Steam Treatment (HWST) were examined.•Heat distribution is similar in both treatments.•HWST reduced the treatment time by 63% and energy consumption by 52%.•Both treatment did not irreversibly harm trees.